Development of CRISPR/Cas9-mediated CD16b-/- and CD32a-/- promyelocytic cell lines to study FcγR signaling in human neutrophils - Cruz-Cárdenas, José Antonio; López-Arredondo, Alejandra; Cázares-Preciado, Jorge Andrés; Rodríguez-Gonzalez, Mabel; Palomares, Laura A.; Brunck, Marion E. G. (Frontiers in Immunology, 2025)
IntroductionNeutrophils use Fc gamma receptors (FcγRs) to recognize IgG-opsonized pathogens, triggering antimicrobial functions including phagocytosis, ROS production, and cytokine release. CD16b, the most abundant FcγR on neutrophils, plays a key role in initiating these responses, while CD32a is another abundant FcγR on neutrophils that contributes to modulating immune functions. CD16b lacks an intracellular domain and its signaling mechanisms remain unclear. The prevalence of the CD16b-deficient phenotype on donor neutrophils is estimated at <1% of the global population, which complicates its study. To address this, we employed CRISPR/Cas9 to generate HL-60-derived neutrophil-like cells deficient for CD16b or CD32a, that facilitate investigation of their respective roles in neutrophil biology.MethodsWe disrupted the FCGR3B or FCGR2A genes using CRISPR/Cas9 in the HL-60 cell line and differentiated clones into neutrophil-like cells using 1.3% DMSO. Functional assays were performed, including phagocytosis, ROS production, SYK phosphorylation, and cytokine responses.Results and discussionBoth CD16b-/- and CD32a-/- HL-60-derived clones maintained neutrophilic differentiation and phagocytic capacity but displayed impaired FcγR-mediated ROS production and SYK phosphorylation, with more pronounced defects in CD16b-/- cells. Cytokine production was altered in both lines, with CD16b-/- cells producing less IL-6 and IL-1β, and CD32a-/- cells producing less TNF-α and IL-10. This model provides new insights into the distinct roles of CD16b and CD32a in neutrophil activation and immune responses.